2012
DOI: 10.1109/jstars.2012.2191146
|View full text |Cite
|
Sign up to set email alerts
|

Mexico City Subsidence Measured by InSAR Time Series: Joint Analysis Using PS and SBAS Approaches

Abstract: International audienceIn multi-temporal InSAR processing, both the Permanent Scatterer (PS) and Small BAseline Subset (SBAS) approaches are optimized to obtain ground displacement rates with a nominal accuracy of millimeters per year. In this paper, we investigate how applying both approaches to Mexico City subsidence validates the InSAR time series results and brings complementary information to the subsidence pattern. We apply the PS approach (Gamma-IPTA chain) and an ad-hoc SBAS approach on 38 ENVISAT image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…Ground subsidence along subways have also been observed in other delta areas, such as Shenzhen [18], Shanghai [17,41], Beijing [19,42,43], and Mexico [44,45]. In different areas, the ground subsidence scales and magnitudes are different.…”
Section: Subsidence Along Subway Lines In Delta Areasmentioning
confidence: 99%
“…Ground subsidence along subways have also been observed in other delta areas, such as Shenzhen [18], Shanghai [17,41], Beijing [19,42,43], and Mexico [44,45]. In different areas, the ground subsidence scales and magnitudes are different.…”
Section: Subsidence Along Subway Lines In Delta Areasmentioning
confidence: 99%
“…All pairs formed had a perpendicular baseline of no greater than 250 m. This small baseline threshold allows maximization of spatial coherence and reduces the phase contribution due to DEM errors (Yan et al, 2012). No threshold was imposed on the temporal baselines, due to the relatively short period of observation covered by the 18 IW scenes (i.e.…”
Section: Generation Of the Differential Interferogramsmentioning
confidence: 99%
“…It was subsequently concluded that the subsidence is the result of extensive groundwater extraction for domestic, industrial and municipal uses (Figueroa Vega, 1976). Numerous publications can be found on the use of multi-temporal DInSAR for monitoring land subsidence in Mexico City using C-band and L-band imagery, such as demonstrated by López-Quiroz et al (2009), Cabral-Cano et al (2010, Cigna et al (2011), Osmanoǧlu et al (2011), Yan et al (2012 and Chaussard et al (2014). In preparation for the Sentinel-1 mission, the city was also included as a case study for the Sentinel-1 like RADARSAT-2 TOPS campaign in 2013, and several Sentinel-1 DInSAR trials were carried out by the InSAR community (e.g., ESA, 2014d;Geudtner, 2014;Lanari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, few applications of this methodology have focused on land subsidence in urban areas (e.g., Aobpaet et al, 2010;Yan et al, 2012).…”
Section: Methodsmentioning
confidence: 99%